PENERAPAN STRATEGI DRTA (DIRECTED READING THINKING ACTIVITY) UNTUK MENINGKATKAN KEMAMPUAN SISWA DALAM MENCARI GAGASAN POKOK KARANGAN NARASI PADA SISWA KELAS IV SDN 003 PAGARAN TAPAH DARUSSALAM - Marnius ' (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This research is motivated by the low ability students in finding ideas principal authorshipnarration in class IV SDN 003 Pagaran Tapah Darussalam. Goals to be achieved in thisresearch is to improve the ability of students in the basic idea for narrative writing in class IVSDN 003 Pagaran Tapah Darussalam through DRTA Strategy (directed reading thinkingactivity) carried out for 1 month. This research was conducted in SDN 003 Pagaran TapahDarussalam. Classes are meticulous researchers are class IV by the number of students asmany as 20 people. The study of this class action commenced in early September 2014. Thisform of research is classroom action research. The research instrument consists ofinstruments teacher and student activity sheets and achievement test. Based on the results ofthe study, the research concluded that the ability to search for the key idea fourth gradestudents of SDN 003 Pagaran Tapah Darussalam can be enhanced through DRTA strategy.This is evident from the increase in the student's ability in finding the key idea of the strategyDRTA before being applied to the second cycle of the second meeting. Known frompreliminary data the average value of students is 63. If the views of classical completeness,there are 30% of students (6) who finished obtaining a minimum value of 65 (according to thestandard KKM), the first cycle the first meeting denganrata average increased to 65, 3%circuitry completeness reach 10 or 50%, while in the second meeting mkembali increased to69.5 by the thoroughness of 12 people or 60% and sikluy II first meeting back in an averageincrease of 75% with the thoroughness of 16 or 80% and increased again in meetings second,reaching 80.5% with 100% completeness. The overall ability of students increased from theinitial tests until the fourth meeting of (20%). Thus, this study was successful